KEHADIRAN MAMALIA PADA SESAPAN (SALT LICK) DI HUTAN LINDUNG TARATAK, KABUPATEN PESISIR SELATAN, SUMATERA BARAT - Novarino, Wilson; Kamilah, Santi N; Nugroho, Agung; Janra, M. Nazri; Silmi, M.; Syafrie, M. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
The study of mammals visitation on salt licks in protected forest of Taratak, SoutheraCoast of West Sumatra was conducted from June to September 2005 (in total 6840hours.camera). Three camera traps were deployed separately on three salt lick areas.Nine species of mammals were recorded during the study. Tapirus indicus was thespecies most often photographed (13.5%), followed by Presbytis melalophos (11.3%) andSus scrofa (9.8%). This study also records the activity of human on salt licks areas. Thenumbers of visitation of mammals on three salt licks area differed, both in the numberof species and the number of individual. The differences of mammal visitation on saltlicks were not affected by size, altitude, and distances from village. The results alsoshowed that there was time segregation when entering the salt licks area, both interrestrial mammals and primates.